PERSEPSI GURU DAN SISWA SMP KOTA PEKANBARU TERHADAP KUALITAS BUKU TEKS PELAJARAN IPA BERBASIS KURIKULUM 2013 UNTUK SMP/MTs KELAS VII TERBITAN KEMENDIKBUD - Mifda Julyana Mifda Julyana; Mariani Natalina Mariani Natalina; Darmadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this study is to know about the image perception of teachers and students of SMP Pekanbaru to the quality of science text book 2013 based curriculum for SMP/MTs VII grade published byKemendikbud. The research was conductedfrom February to July 2014. The sample in this study amounted to 12 science teachers SMP at selected by the sample saturated, while SMP students of VII grade totaled 588 randomly selected people. Data collection instrumentused was a questionnaire enclosed and open questionnaire. Enclosed questionnaire for science teachers SMP consists of 50 items that statement is divided into 5 indicators, namely the feasibility of the content, presentation material, linguistic, books graphic, and conformity with the curriculum. Meanwhile, enclosed questionnaire for SMP students of VII grade consists of 30 items divided into a statement that four indicators, namely the feasibility of the content, presentation material, linguistic, and books graphic. The collected data were analyzed descriptively. The perceptions of science teachers SMP picture Pekanbaru to quality science text book are averaging 3,19 classified into good category. And so it is with the perceptions of students VII grade SMP Pekanbaru to the quality of Pekanbaru science text books have averaged 3,22 with good category.Keywords:perception, text books, curriculum 2013